Beyond Teaching Languages for Communication—Humanistic Perspectives and Practices - Byram, Michael; Porto, Melina; Yulita, Leticia (Languages (Basel), 2023)
Our purpose is to trace and explain theoretical and practical developments in foreign/world language teaching over the last decade or more. Language teaching in its modern form, from the Reform Movement of the late 19th century, has focused upon the need for learners to learn or acquire a foreign language in order to use it for communication. Other purposes involve language learning as an intellectual exercise, the development of a language faculty, and opening (young) people’s eyes to new worlds by introducing them to other countries. Here, we argue that these purposes are reasonable and enriching, but only if they are combined. We suggest that, by taking a humanistic perspective, language teaching can go beyond communication as a dominant purpose. This humanistic perspective is realised through two complementary developments. One is to emphasise that learners are members of various communities, including their local community, their national community, and a world community. The second is to pay attention to the fact that learners bring to the classroom their concerns and fears, especially in times of crisis. Language teachers, who are not only instructors in skills but educators of the whole person, should respond to their learners’ needs both as denizens of their society and as unique individuals. We first explain the theoretical framework and how it has evolved and then describe two experimental projects, one which focuses on the societal needs and one which adds to this a response to the affective needs of learners. We finally discuss how a recent controversy might be addressed in the language teaching class.